Estimated Costs and Regional Economic Impacts of the Oriental Fruit Fly (Bactrocera dorsalis) Outbreak in Miami-Dade County, Florida - Sergio Alvarez; Edward A. Evans; Alan W. Hodges (EDIS, 2016)
Oriental fruit flies, very destructive pests of fruits, were first detected in the Redland area of Miami-Dade County on August 26, 2015, and as of January 2016, 165 flies had been captured. This triggered an eradication program and establishment of a quarantine area composed of agricultural operations and nonagricultural properties, such as residential and commercial areas. As part of the effort to eradicate the fruit fly, growers and packers in the quarantine area are required to sign a compliance agreement that outlines the procedures necessary for harvesting, handling, and postharvest processing of agricultural products that may serve as hosts for any life cycle of the fruit fly. This 12-page fact sheet provides estimates of the direct and indirect losses to Florida’s agriculture and related sectors as a result of the outbreak and ensuing quarantine and eradication programs. Written by Sergio Alvarez, Edward A. Evans, and Alan W. Hodges, and published by the UF Food and Resource Economics Department, April 2016.